Revealing the effect of iron content on the microstructure evolution, mechanical properties and corrosion resistance of the A356-T6 aluminum alloys - Yongquan Liu; Meng Wang; Yang Cao; Jiajing Peng; Dongyang Yang; Dongfu Song; Bright O. Okonkwo; Jianqiu Wang; Enhou Han (Journal of Materials Research and Technology, 2024)
Recently, the A356 alloy has been widely used in various fields owing to its low cost, excellent mechanical properties, and formability. However, the existence of Fe can significantly affect the comprehensive properties of A356 alloys. The present study systematically investigated the effects of different Fe contents on the microstructures, mechanical properties, and corrosion resistance of recycled A356-T6 alloys using different characterization technologies, including optical microscopy (OM), scanning electron microscopy (SEM), electron probe X-ray micro-analysis (EPMA), tensile tests, and electrochemical tests. The results suggest that the volume fraction of the Fe-rich particles gradually increases with increasing Fe content, and their morphologies display a transformation from granular and short rod-like to acicular and Chinese-script. While the ultimate tensile strength of the A356-T6 alloys with different Fe contents remained relatively stable, their yield strengths gradually increased. Meanwhile, the elongation experiences a stepwise drop owing to the increase in the number fraction of brittle needle-shaped β-Al5FeSi (β-Fe) phases. Moreover, the results of the electrochemical tests suggest that a dramatic decline in the corrosion potential and an increase in the self-corrosion current density occurred with an increase in the Fe content, resulting in a considerable deterioration of the corrosion resistance.